Real-Time insight into in vivo redox status utilizing hyperpolarized [1-(13)C] N-acetyl cysteine - Yamamoto, Kazutoshi (Sci Rep, 2021)
Drastic sensitivity enhancement of dynamic nuclear polarization is becoming an increasingly critical methodology to monitor real-time metabolic and physiological information in chemistry, biochemistry, and biomedicine. However, the limited number of available hyperpolarized (13)C probes, which can effectively interrogate crucial metabolic activities, remains one of the major bottlenecks in this growing field. Here, we demonstrate [1-(13)C] N-acetyl cysteine (NAC) as a novel probe for hyperpolarized (13)C MRI to monitor glutathione redox chemistry, which plays a central part of metabolic chemistry and strongly influences various therapies. NAC forms a disulfide bond in the presence of reduced glutathione, which generates a spectroscopically detectable product that is separated from the main peak by a 1.5 ppm shift. In vivo hyperpolarized MRI in mice revealed that NAC was broadly distributed throughout the body including the brain. Its biochemical transformation in two human pancreatic tumor cells in vitro and as xenografts differed depending on the individual cellular biochemical profile and microenvironment in vivo. Hyperpolarized NAC can be a promising non-invasive biomarker to monitor in vivo redox status and can be potentially translatable to clinical diagnosis.